Quizlet: Exploring Pedagogical Dynamics in Remote EFL Vocabulary Acquisition - Amrullah, Ahmad Zubaidi (Universitas Muhammadiyah Jember, 2024)
The rapid transition to distance education, prompted by the global COVID-19 outbreak, has compelled educators to integrate CALL/MALL. Within the context of remote learning, this study examines Quizlet, a digital platform used for learning through flashcards, to determine its instructional advantages and limitations in facilitating the acquisition of vocabulary for EFL students. The study employed a case study of 47 Indonesian high school students participating in an English extracurricular club using two surveys and in-depth interviews to acquire insights about students' attitudes and experiences with Quizlet. Ten sets of flashcards covering fundamental and common words were used for a full semester of remote instruction. The findings indicate that Quizlet contributed positively to vocabulary acquisition. Students performed satisfaction in its various features, user-friendly interface, ease of memorization, accessibility, and motivational aspects of Quizlet. Despite the challenges encountered in terms of connectivity with the live quiz function, alternative methods such as self-tests were utilized. The investigation demonstrates that Quizlet's multimodal learning experience enhances the learning of EFL vocabulary. Nevertheless, the limitations linked to internet connectivity necessitate careful consideration. It underscores the importance of educators addressing potential hindrances, particularly those pertaining to the internet, in order to achieve successful remote teaching.